2008
DOI: 10.1093/jeg/lbn052
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking human capital, creativity and urban growth

Abstract: Do jobs follow people or do people follow jobs? A number of currently prominent approaches to urbanization respond to this question by privileging the role of individual locational choice in response to amenity values as the motor of contemporary urban growth. Amenities, it is often said, have an especially potent effect on the migration patterns of individuals endowed with high levels of human capital. However, these approaches raise many unanswered questions. Theories that describe urban growth as a response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
476
4
20

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 712 publications
(524 citation statements)
references
References 40 publications
24
476
4
20
Order By: Relevance
“…In general, endogenous models of regional growth have followed in the footsteps of Romer (1986; and Lucas (1988), with a focus on the role of endowments of knowledge and human capital in explaining innovation and growth differentials (Andersson and Karlsson 2007;Storper 2010;Storper and Scott 2009;Capello and Nijkamp 2009;Harris 2011). As indicated earlier, more recently, there has been significant attention given to adding the role of entrepreneurs into these equations, particularly through the inclusion of the concept of entrepreneurship capital (Audretsch and Keilbach 2004a;2004b;.…”
Section: Endogenous Regional Growth Entrepreneurship and Network Capmentioning
confidence: 99%
“…In general, endogenous models of regional growth have followed in the footsteps of Romer (1986; and Lucas (1988), with a focus on the role of endowments of knowledge and human capital in explaining innovation and growth differentials (Andersson and Karlsson 2007;Storper 2010;Storper and Scott 2009;Capello and Nijkamp 2009;Harris 2011). As indicated earlier, more recently, there has been significant attention given to adding the role of entrepreneurs into these equations, particularly through the inclusion of the concept of entrepreneurship capital (Audretsch and Keilbach 2004a;2004b;.…”
Section: Endogenous Regional Growth Entrepreneurship and Network Capmentioning
confidence: 99%
“…As discussed by Storper and Scott (2009) some studies (including Florida and Gates, 2001;Florida, 2002) found a positive association between diversity and regional growth, under the assumption that a tolerant milieu is more likely to be conducive to creativity provided that talented people have a preference for tolerance. However, more recent studies by some of the same authors (e.g.…”
Section: Drivers Of Regional Growthmentioning
confidence: 99%
“…A likely stronger correlation is instead to be expected between tolerance and low barriers to entry for recent immigrants, because a tolerant atmosphere reduces the likelihood of potential social and cultural frictions and attenuates the typical perception 6 that immigrants are getting jobs that would have otherwise been taken by natives (de Palo, Faini and Venturini, 2006). According to Storper and Scott (2009), accumulation of high levels of human capital in 'tolerant' regions which prove successful both to attract the creative class and to economically and socially assimilate recent immigrants might prove successful in turning creativity into commercially exploitable knowledge, therefore leading to increased regional economic dynamism in the guise of employment growth.…”
Section: Drivers Of Regional Growthmentioning
confidence: 99%
“…the extent to which different types and forms of knowledge can be combined and mixed to create value -is similar to Romer's (1996) idea of creating new recipes from existing knowledge. As Storper and Scott (2009) argue 'knowledge has a tendency to grow indefinitely, for it can be endlessly re-used, is extremely leaky (and hence its circle of users continually expands), and can be combined and recombined in virtually unlimited ways.' (p. 148).…”
Section: The Nature Of Accessed Knowledgementioning
confidence: 99%